Detection of kobuvirus RNA in Japanese domestic dogs - SOMA, Takehisa; MATSUBAYASHI, Makoto; SASAI, Kazumi (Journal of Veterinary Medical Science, 2016)
To investigate whether kokuvirus is present in Japanese dogs, we examined the fecal samples obtained from 94 diarrheal household dogs and 50 clinically healthy kenneled dogs by RT-PCR. The gene was detected in 37.2% and 48.0% in the former and the latter, respectively, suggesting that canine kobuvirus (CaKoV) is circulating among Japanese dogs. From the result of the latter, however, CaKoV may not be a primary pathogen. Furthermore, all gene-positive dogs were purebreds aged four months or younger. This finding suggests that CaKoV endemic is confined in multi-dog environments, and the dogs have a strong age-dependent resistance to CaKoV.